Comparative Studies on Khaya. A. Juss.(meliaceae) in Nigeria (2006)
Comparative phytochemical, microscopical and chemomicroscopica! studies were carried out on the genus Khaya with the aim of obtaining useful characters for the identification and delimitation of species boundaries. Tannins and saponins were present In all the species while phenols were detected in all except K. grandlfollola. Protein and anthraquinones were present in the bark of all. iba species. Carbohydrate is present in all the species except in the hark of K. Ivoriensls. Flavonoids and phlobatannins were absent in all the taxa. Microscopical examination of the powdered bark revealed different types and shapes of lignified sclerelds, abundant distribution of prismatic calcium oxalate crystals, druses, lignified cork-cells, fibres, medullary rays and parenchyma cells which may contain starch grains.